Microbial Extracellular Polymeric Substances: Ecological Function and Impact on Soil Aggregation - Costa, Ohana Y. A.; Raaijmakers, Jos M.; Kuramae, Eiko E. (Frontiers in Microbiology, 2018)
A wide range of microorganisms produce extracellular polymeric substances (EPS), highly hydrated polymers that are mainly composed of polysaccharides, proteins and DNA. EPS are fundamental for microbial life and provide an ideal environment for chemical reactions, nutrient entrapment and protection against environmental stresses such as salinity and drought. Microbial EPS can enhance the aggregation of soil particles and benefit plants by maintaining the moisture of the environment and trapping nutrients. In addition, EPS have unique characteristics, such as biocompatibility, gelling and thickening capabilities, with industrial applications. However, despite decades of research on the industrial potential of EPS, only a few polymers are widely used in different areas, especially in agriculture. This review provides an overview of current knowledge on the ecological functions of microbial extracellular polymeric substances (EPS) and their application in agricultural soils to improve soil particle aggregation, an important factor for soil structure, health and fertility.